2008 38th Annual Frontiers in Education Conference 2008
DOI: 10.1109/fie.2008.4720285
|View full text |Cite
|
Sign up to set email alerts
|

Engineering undergraduate persistence and contributing factors

Abstract: The engineers of 2020 must be technically sound in their disciplines, global citizens, as well as aspirational, ethical leaders. To foster a new generation of engineering talent, modern curricula must advance strong analytical skills, teamwork, professionalism, and leadership. However, new curriculum with poor student retention cannot be deemed successful. We believe we possess the key components of a successful program, such as well-designed curricula, dedicated faculty and strong support services, yet many s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 18 publications
2
43
0
Order By: Relevance
“…These findings were in line with other research in the literature. For example, Haag, Hubele, Garcia, and Mcbeath (2007) found that the complaints of their engineering participants about inadequate advising were partly due to their advisors' incorrect information about course requirements. Similarly, Young-Jones et al (2013) stressed the importance of the availability of the advisor for his/her advisees on their feeling of being academically supported.…”
Section: Attitudes Of the Studentsmentioning
confidence: 99%
“…These findings were in line with other research in the literature. For example, Haag, Hubele, Garcia, and Mcbeath (2007) found that the complaints of their engineering participants about inadequate advising were partly due to their advisors' incorrect information about course requirements. Similarly, Young-Jones et al (2013) stressed the importance of the availability of the advisor for his/her advisees on their feeling of being academically supported.…”
Section: Attitudes Of the Studentsmentioning
confidence: 99%
“…Included in this report is the recommendation for more studies on the K-12 students' transition to college to better understand the acquisition of important interdisciplinary cross-cutting concepts in STEM their influence on retention and persistence of students in the STEM disciplines. Furthermore, with respect to students' success in college especially in STEM disciplines, students switch out of these disciplines due to their inadequate high-school preparation for challenging math or science courses (Seymour & Hewitt, 2000, Haag, Hubele, Garcia & McBeath, 2007. Among other reasons for students' failure to persist in college STEM programs, Haag, et al (2007) note that students' under preparation is caused by deficiencies in content and domain specific depth of knowledge, and lack of students' skills and habits in problem solving within science and mathematics topics (p. 932).…”
Section: The Potential Of I-stem Ed For Improving Student Achievementmentioning
confidence: 99%
“…Furthermore, with respect to students' success in college especially in STEM disciplines, students switch out of these disciplines due to their inadequate high-school preparation for challenging math or science courses (Seymour & Hewitt, 2000, Haag, Hubele, Garcia & McBeath, 2007. Among other reasons for students' failure to persist in college STEM programs, Haag, et al (2007) note that students' under preparation is caused by deficiencies in content and domain specific depth of knowledge, and lack of students' skills and habits in problem solving within science and mathematics topics (p. 932). Students' SAT scores and high-school standardized test scores do not reflect these types of deficiencies.…”
Section: The Potential Of I-stem Ed For Improving Student Achievementmentioning
confidence: 99%
“…Retention of students in engineering studies is currently of interest worldwide as well as in South Africa (Hartman & Hartman, 2006;Suresh, 2006/7;Haag, Hubele, Garcia & McBeath, 2007;Scott, Yeld & Hendry, 2007;Allie et al, 2009). One approach to the issue of student retention suggests that lack of development of "engineering identity" results in attrition as students leave tertiary studies or move to other fields of study (Allie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%